2020
DOI: 10.3389/fped.2020.616731
|View full text |Cite
|
Sign up to set email alerts
|

Complement Inhibition in Severe COVID-19 Acute Respiratory Distress Syndrome

Abstract: Most children with COVID-19 have asymptomatic or mild illness. Those who become critically ill suffer from acute respiratory distress syndrome (ARDS) and acute kidney injury (AKI). The rapid deterioration of lung function has been linked to microangiopathic and immune-mediated processes seen in the lungs of adult patients with COVID-19. The role of complement-mediated acute lung injury is supported by animal models of SARS-CoV, evaluation of lung tissue in those who died from COVID-19 and response of COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A recently published case report demonstrated that C5a was not blocked in a patient who had been treated with the C5 inhibitor eculizumab. 4 Furthermore, a recently published study of eculizumab for treatment of patients with severe COVID‐19 5 showed no difference in C5a concentrations between eculizumab‐treated and eculizumab‐free patients at day 1 and day 7. 6 Another potential advantage of direct inhibition of C5a compared with upstream inhibition, such as C5 or C3 inhibition, is that C5b and C5b‐9 and the membrane attack complex (MAC) formation are left intact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published case report demonstrated that C5a was not blocked in a patient who had been treated with the C5 inhibitor eculizumab. 4 Furthermore, a recently published study of eculizumab for treatment of patients with severe COVID‐19 5 showed no difference in C5a concentrations between eculizumab‐treated and eculizumab‐free patients at day 1 and day 7. 6 Another potential advantage of direct inhibition of C5a compared with upstream inhibition, such as C5 or C3 inhibition, is that C5b and C5b‐9 and the membrane attack complex (MAC) formation are left intact.…”
Section: Discussionmentioning
confidence: 99%
“…Especially thrombin, but also other enzymes will be abundant and highly active. A recently published case report demonstrated that C5a was not blocked in a patient who had been treated with the C5 inhibitor eculizumab 4 . Furthermore, a recently published study of eculizumab for treatment of patients with severe COVID‐19 5 showed no difference in C5a concentrations between eculizumab‐treated and eculizumab‐free patients at day 1 and day 7 6 .…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore hypothesized that excessive complement activation contributes to disease progression and severity (126). Indeed, complement inhibition using antibodies directed against C5a (127), C5 (128,129), and C3 (130) are currently being tested.…”
Section: Dysregulation Of the Complement Cascadementioning
confidence: 99%
“…The complement system is a key part of the innate immune system which plays an important role in defense against foreign pathogens such as viruses but, in addition to being an important part of the immune defense system, it plays a critical role in promoting the inflammatory process that leads to organ dysfunction [21]. Although several studies have been carried out on the complement system in COVID-19 and its relationship with clinical outcomes [5,6,8,12,25], they did not indicate a clear protective or adverse effect of this system.…”
Section: Introductionmentioning
confidence: 99%